Recent advances in anterior pituitary hormones and metabolic-associated fatty liver disease - Liu, Changqing; Long, Yuanyuan; Liu, Junjun; Song, Yongfeng (Frontiers in Endocrinology, 2025)
The classical theory of the pituitary–target gland axis suggests that the hormones secreted by the pituitary gland only regulate the synthesis and secretion of target gland hormones, while the target gland hormones act on the tissues of the body to achieve biological functions. However, recent studies have shown that anterior pituitary hormone receptors are also expressed on the surface of hepatocytes. This suggests that anterior pituitary hormones may act directly on hepatocytes to exert regulatory effects independent of target hormones. The review systematically summarizes the mechanisms and effects of thyroid-stimulating hormone (TSH), follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), adrenocorticotropic hormone (ACTH), growth hormone (GH), and melanocyte-stimulating hormones (MSH) on liver metabolism and their roles in the pathogenesis of Metabolic-Associated Fatty Liver Disease (MAFLD). It is hoped that this will provide new insights into the prevention and treatment of MAFLD.